Is the mental health of couples with twins more at risk? Results from an Italian cohort study - Bonanni, Giulia; Longo, Valentina Laurita; Airoldi, Chiara; Meli, Federica; Familiari, Alessandra; Romanzi, Federica; Pellegrino, Marcella; Visconti, Daniela; Serio, Annamaria; Lanzone, Antonio; Bevilacqua, Elisa (Frontiers in Psychiatry, 2024)
Our retrospective study aimed to investigate whether parents of twins encounter heightened psychological and emotional distress one year after childbirth, in comparison to parents of singletons within an Italian cohort. Exclusion criteria included multiparity, preterm birth, congenital anomalies, stillbirth, >2 fetus pregnancies, and pre-existing maternal mental health disorders. Out of the 300 couples (600 parents) invited to participate, 286 parents (158 mothers, 128 fathers) successfully completed a self-administered survey. We analyzed three scores separately for mothers and fathers, differentiating between singleton and twin pregnancies: the Edinburgh Postnatal Depression Scale (EPDS) score, the State and Trait Anxiety Inventory (STAI)-Y1 score, and the STAI-Y2 score. Logistic models were used to assess the influence of age, BMI, marital status, education, and employment on the three binary scores (EPDS, STAI-Y1, and STAI-Y2), revealing no significant differences in absolute scores between parents of singletons and twins. Paired analysis revealed significantly higher EPDS (mean increase: 3.8, SD: 6.5), STAI-Y1 (mean increase: 5.4, SD: 12.5), and STAI-Y2 (mean increase: 4.5, SD: 12.4) scores for mothers (p < 0.0001). Approximately 10% of women and 8% of men reported suicidal thoughts. Contrary to expectations, no substantial psychological differences emerged between parents of twins and singletons. Adjusting for confounders through univariate analysis maintained nonsignificant trends. Nevertheless, caution in interpretation is warranted due to strict inclusion criteria favoring twin pregnancies with better outcomes. Unintended bias could have resulted from routine psychological support offered to mothers of twins in our clinic. This presents an important framework for future research, including randomized controlled trials comparing parents of multiples with psychological support to those without. Finally, the elevated prevalence of depression symptoms and suicidal thoughts in our cohort underscores the importance of mental health during pregnancy and early parenting. We advocate for the screening of parents for postpartum depression and various psychological conditions, encompassing a spectrum of anxiety disorders. Those at elevated risk of mental distress should be proactively offered appropriate support.